One World, One Faith: The Quest for Unity in Julian Huxley's Religion of Evolutionary Humanism - Phillips, Paul T. (Journal of the history of ideas, 2007)
, Sir Julian Huxley (1887-1975), celebrated British scientist and philosopher, strove through most of his career to establish a non-theistic, rationalist belief system to replace Christianity and other world religions. Believing that the twentieth century provided a unique opportunity for this to happen, evolutionary humanism, as he termed his secular faith, gave direction to most of Huxley's diverse activities as a public intellectual. Rooted in evolutionary science, combined with Idealism, liberal values and a profound belief in progress, Huxley's vision was also suffused with a strong desire for unity in human affairs. This paper examines that quest for unity, the purposes it served, and its reception.